Development of Audiovisual-Based PowToon Animation Video on Chemical Bonds for Tenth Grade - Akmalia Mutiara Dewi; Agus Kamaludin (Jurnal Penelitian Pendidikan IPA, 2022)
This research aimed to develop an audiovisual-based PowToon animation video on the subject matter of chemical bonds and analyze the quality of the audiovisual-based animated video as learning media to study chemical bonds based on the assessment of material experts, media experts, chemistry teachers, and students’ responses. This research used development research methods (R&D) with a 4D development model (Define, Design, Development, and Dissemination). However, the 4D development model was limited to the dissemination stage in this research. The product is an animated video, which is in the form of mp4, containing chemical bond materials. Based on product quality assessment by a material expert, it gained a percentage of 84.375% with very good (VG) category; from the media expert’s assessment, it obtained a percentage of 96.428% with very good (VG) category; and according to assessment by chemistry teachers of high school, it got a percentage of 98.48% in the very good (VG) category. The product was responded to positively by students with a percentage of 95%. Based on the results of assessments, the animated video can be used as an alternative media for the chemistry learning process in the classroom